Marketing for information products and services promotion: Brasil republic presidency library’ case study: case study of the Library of the Presidency of the Republic - Baptista, Sofia Galvão (2009)
The application of the theory of marketing as management resource for libraries and information services is demonstrated by the Brasil Republic Presidency Library in order to confirm marketing concepts application for the social area. The services provided by the library was evaluated to observe the use of promotion activities, public relations, merchandising, advertising, incentives, atmosphere and others marketing techniques. It was found that the library planned and used various promotion techniques: atmosphere, services dissemination, public relations with projects aimed to an specific audience, and others actions to improve the user and the library relationship.